Bulbar respiratory activity during defensive airways reflexes in cats - Jakus, J; Tomori, Z; Stránsky, A; Boselová, L (Acta physiologica Hungarica, 1987)
Experiments in anaesthetized nonparalyzed cats indicated that mechanical stimulation of the airways and a longitudinal split of the brainstem cause marked alterations of the regulatory function of the bulbar respiratory neurones. The resulting changes in breathing and in defensive airways reflexes depend on intactness of the relevant structures of both halves of the "respiratory centre" and their interconnections.
Keywords: Physical Stimulation; kočky; kýchání; Respiration; Medulla Oblongata; Reflex; akční potenciály; zvířata; Action Potentials; neurony; medulla oblongata; dýchání; decerebrační rigidita; fyzikální stimulace; reflex; Cough; Neurons; Sneezing; Cats; kašel; Animals; Decerebrate State